The effects of aspect, directional heating and depth on bedrock temperatures and the potential relationship with thermal fatigue weathering - Breytenbach, Izak Johannes (Rhodes University, Faculty of Science, Department of Geography)
Geomorphological weathering processes and their relationship with temperature fluctuations are frequently researched. These research efforts are mostly restricted to surface conditions where soils, loose-lying rocks or rock outcrops are assessed. However, there is a shortcoming in the understanding of the thermal properties in a rock mass, particularly in the upper metres below the surface, as this has not been investigated or researched in any great detail. The research reported here is unique in this regard as it exploited the use of rotary core boreholes in tillite bedrock in the Karoo (Western Cape, South Africa) which were drilled as part of an invasive materials investigation for a proposed new hard rock quarry to supply road stone. Temperature data were captured on a bedrock ridge hosting tillite outcrop with a strong east to west orientation. The site work was done in two separate phases. The initial phase of research saw data being captured for one year on two aspects (i.e. north and south) at a depth of 0.3 m. This was followed by the second (more detailed) phase, where three aspects were assessed (i.e. north, south and a flat crest), but at depths of 0.3 m, 2.0 m and 6.0 m, totalling nine data acquisition points. The second investigation phase gathered data for seven months. Supplementary weather data were also captured for the site. Subsequent data analyses revealed that there is much to learn about the thermal behaviour of bedrock in the upper metres below the surface, and that the temperature properties or thermal regimes are not as simple as often assumed. Temperature differences related to aspect are not only surficial, but are transmitted to underlying bedrock, and notable temperature differences were measurable to a depth of at least 6.0 m. Seasonal temperature fluctuations also have a pronounced effect on the rock mass temperatures and it was proven that deeper parts of the bedrock accumulate and dissipate heat at different (i.e. retarded) rates compared with shallower parts of the rock mass, creating suitable thermal conditions to induce thermal fatigue. Thermal properties were also proven to be non-linear. During analyses, the concept of temperature inversions was proven, whereby one part of the bedrock becomes hotter or cooler relative to another/adjacent part of the bedrock, compared with its earlier temperature state. It was argued that these temperature inversions may exacerbate thermal fatigue. This research proved that aspect (i.e. directional heating) and depth need to be considered when analysing thermal regimes in a rock mass, as these have a distinct influence. The effects which manifest themselves create suitable conditions for thermal fatigue, not only near the surface but also at depth in the bedrock. Lastly, the effects of meteorological conditions on shallow bedrock temperatures were assessed. Preliminary findings suggest that boundary conditions and meteorological processes may indeed affect shallow bedrock temperatures, but only under certain circumstances and not to the same extent as reported in the literature for conditions researched at the surface. Wind temperature relative to the rock temperature, as well as a combination of wind and rain were found to be the most significant factors.
Keywords: Weathering -- South Africa -- Karoo; Shields (Geology) -- South Africa -- Karoo; Shields (Geology) -- Thermal properties; Tillite -- South Africa -- Karoo